2017
DOI: 10.1051/0004-6361/201730675
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and evolution of vertically polarised transverse loop oscillations by coronal rain

Abstract: Context. Coronal rain is composed of cool dense blobs that form in solar coronal loops and are a manifestation of catastrophic cooling linked to thermal instability. The nature and excitation of oscillations associated with coronal rain is not well understood. Aims. We consider observations of coronal rain in a bid to elucidate the excitation mechanism and evolution of wave characteristics. Methods. We analyse IRIS and Hinode/SOT observations of an oscillating coronal rain event on 17 Aug 2014 and determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…The rain, emitting in chromospheric optical lines, allows a high resolution window into wave processes within the loops. Low amplitude kink oscillations are commonly seen in these structures (Verwichte and Kohutova 2017), including cases of amplification (Antolin and Verwichte 2011) or steady oscillations (Kohutova and Verwichte 2016).…”
Section: Kink Oscillations In Loops Undergoing Coolingmentioning
confidence: 99%
See 2 more Smart Citations
“…The rain, emitting in chromospheric optical lines, allows a high resolution window into wave processes within the loops. Low amplitude kink oscillations are commonly seen in these structures (Verwichte and Kohutova 2017), including cases of amplification (Antolin and Verwichte 2011) or steady oscillations (Kohutova and Verwichte 2016).…”
Section: Kink Oscillations In Loops Undergoing Coolingmentioning
confidence: 99%
“…In large loop oscillations, the ponderomotive force could affect the phenomenon of the coronal rain (Verwichte et al 2017), but it is probably not the primary reason for the observed sub-ballistic motions of the plasma blobs (Antolin and Rouppe van der Voort 2012). The ponderomotive force could be a possible cause of the first ionisation potential (FIP) effect, related to the enhancement or depletion, respectively, in coronal abundance with respect to photospheric values of elements with FIP below about 10 eV (Laming 2015).…”
Section: Field-aligned Flows Driven By the Ponderomotive Force In Kink Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…These MHD oscillations could be identified in the EUV/SXR imaging observations (Nakariakov et al, 1999;Aschwanden et al, 2002;Shen et al, 2013;Goddard & Nakariakov, 2016), and in the spectroscopic observations (Kliem et al, 2002;Mariska, 2005;Li et al, 2015a). The detected periods vary from a few seconds to minutes Schrijver et al, 2002;Tian et al, 2016;Verwichte & Kohutova, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This includes the observation of transverse loop oscillations, which were first observed in connection with eruption events by TRACE (Aschwanden et al 1999;Nakariakov et al 1999) and are routinely observed since (e.g. Verwichte et al 2009;Van Doorsselaere et al 2008;White et al 2012a;Verwichte & Kohutova 2017). MHD wave theory reveals these oscillations to be fast magnetoacoustic in nature that exhibit periodic coherent displacements of the loop axis in a quasi-incompressible manner (Edwin & Roberts 1983;Nakariakov & Ofman 2001;Aschwanden et al 2002;Verwichte et al 2004).…”
Section: Introductionmentioning
confidence: 98%